2000
DOI: 10.1016/s0002-9270(00)00918-7
|View full text |Cite
|
Sign up to set email alerts
|

The proportion of upper gastrointestinal symptoms in the community associated with helicobacter pylori, lifestyle factors, and nonsteroidal anti-inflammatory drugs

Abstract: H. pylori is significantly associated with dyspepsia and may be responsible for 5% of upper gastrointestinal symptoms in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
7
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 0 publications
7
63
7
2
Order By: Relevance
“…That was in contrast to one finding which indicated a harmful effect of smoking [56]. In this study coffee or tea intake has not been shown to be related to the presence of Dyspepsia similarly studied in rural Asia [57].…”
Section: Discussioncontrasting
confidence: 96%
“…That was in contrast to one finding which indicated a harmful effect of smoking [56]. In this study coffee or tea intake has not been shown to be related to the presence of Dyspepsia similarly studied in rural Asia [57].…”
Section: Discussioncontrasting
confidence: 96%
“…We did not find any significant association between these factors and dyspepsia, but we did observe the lowest prevalence of smoking and alcohol consumption in the group with the highest prevalence of dyspepsia. �imilar findings have been reported previously (26) and have been explained by the fact that the abstinence of putative offending agents is a common recommendation for dyspeptic patients in the early stages of the development of dyspepsia. The most likely explanation for our findings is therefore that lifestyle modifications introduced in the past in order to alleviate dyspeptic symptoms were the cause of our findings.…”
Section: Discussionsupporting
confidence: 81%
“…Although 5% of the cases of dyspepsia in the community are attributable to infection with H. pylori, 53 the effect of eradication therapy on the symptoms of functional dyspepsia is modest. In a meta-analysis of 17 randomized trials, In the presence of a background genetic disposition, a type 2 helper T (Th2)-cell response may be activated in the duodenum, possibly by allergens or pathogens, which cross through the gut epithelium.…”
Section: H Pylori Eradication Therapymentioning
confidence: 99%